Statistical adjustment of data - Deming, W. Edwards (Dover, 2014)
Introduction to basic statistical concepts and to concept of "adjustment" also covers solution by least squares of more complicated problems and takes into account the propagation of error, general problem of least squares, and conditions without parameters.